PENGARUH FASILITAS, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Coffee Shop di Kota Semarang) - Ningtias, Devi Rosita; Indriyatni, Lies; Widodo, Untung (STIE PENA, 2022)
This study aims to examine and analyze the effect of facilities, service quality, and promotion on customer satisfaction at the Coffee Shop in Semarang City. The population in this study are consumers who have visited and made purchases at a coffee shop in the city of Semarang. The sample in this study was taken using purposive sampling technique with the criteria of consumers who have visited and bought at least 2 times a purchase. Samples were taken using the opinion of Ferdinand. The sample size is determined 25 times the independent variable, so that 3 x 25 = 75 respondents. Therefore, this study determined 75 respondents. Data were analyzed using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test, and determination coefficient test (R2). The results showed that facilities had no effect on customer satisfaction, service quality had a positive and significant effect on customer satisfaction, promotion had no effect on customer satisfaction.Keywords: Facilities, Service Quality, Promotion and Customer Satisfaction